The Power of Artificial Intelligence on Sports - İnce Yenilmez, Meltem; Ersöz, Gözde (Sport Economics Research, 2025)
This article explores the broader role that artificial intelligence (AI) will play in the changing sports industry, focusing on how it will impact areas such as player performance, management, strategy formulation, and access to fans. As demonstrated by technologies such as FIFA sideline technology and video-assisted refereeing (VAR), the fusion of artificial intelligence and sports is driving a redefinition of traditional concepts of justice and human decision-making, resulting in greater reliance on data and objective decision-making processes. The study identifies fundamental issues in the practical and economic elements of sports, including the utilisation of artificial intelligence (AI) and strategic planning. The present study traces the evolution of scientific discourse through a detailed literature analysis of AI in sports from 1975 to 2023. The present study explores the evolution of artificial intelligence applications and their influence on the digital economy. To this end, an investigation is conducted into patterns of academic publications, encyclopedia editions, and collaborative networks. A notable increase in academic demand has also been observed since 2017, suggesting a growing public awareness of AI's revolutionary potential. This study makes a theoretical contribution to the understanding of the integration of AI into the sports ecosystem. It has the potential to assist sports organisations and policymakers in addressing ethical issues and jobs created by the use of AI.